Monocot and dicot MLO powdery mildew susceptibility factors are functionally conserved in spite of the evolution of class-specific molecular features. Issue 1 (December 2015) - Appiano, Michela; Catalano, Domenico; Santillán Martínez, Miguel; Lotti, Concetta; Zheng, Zheng; Visser, Richard; Ricciardi, Luigi; Bai, Yuling; Pavan, Stefano
Abstract Background Specific members of the plant Mildew Locus O (MLO) protein family act as susceptibility factors towards powdery mildew (PM), a worldwide-spread fungal disease threatening many cultivated species. Previous studies indicated that monocot and dicot MLO susceptibility proteins are phylogenetically divergent. Methods A bioinformatic approach was followed to study the type of evolution of Angiosperm MLO susceptibility proteins. Transgenic complementation tests were performed for functional analysis. Results Our results show that monocot and dicot MLO susceptibility proteins evolved class-specific conservation patterns. Many of them appear to be the result of negative selection and thus are likely to provide an adaptive value. We also tested whether different molecular features between monocot and dicot MLO proteins are specifically required by PM fungal species to cause pathogenesis. To this aim, we transformed a tomato mutant impaired for the endogenousSlMLO1 gene, and therefore resistant to the tomato PM speciesOidium neolycopersici, with heterologousMLO susceptibility genes from the monocot barley and the dicot pea. In both cases, we observed restoration of PM symptoms. Finally, through histological observations, we demonstrate that both monocot and dicot susceptibility alleles of theMLO genes predispose to penetration of a non-adapted PM fungal species in plant epidermal cells. Conclusions With this study, we provide insights on the evolution and function ofMLO genes involved in the interaction with PM fungi. With respect to breeding research, we show that transgenic complementation assays involving phylogenetically distant plant species can be used for the characterization of novelMLO susceptibility genes. Moreover, we provide an overview of MLO protein molecular features predicted to play a major role in PM susceptibility. These represent ideal targets for future approaches of reverse genetics, addressed to the selection of loss-of-function resistant mutants in cultivated species.